PROBLEMATIKA PERBEDAAN LATAR BELAKANG MAHASISWA DI PRODI PSIKOLOGI ISLAM FDKI IAIN SAS BANGKA BELITUNG - Tsana, Al-Fiyyah (JURNAL DIALOKA: Jurnal Ilmiah Mahasiswa Dakwah dan Komunikasi Islam, 2022)
This research examines the problems of different backgrounds of students in the Islamic psychology study program, Faculty of Da’wah and Islamic Communication, Syaikh Abdurrahman Siddik Islamic Institute, Bangka Belitung. This research aims to describe the background and explain the problems that occur in the lecture process at the Islamic psychology study program, Faculty of Da’wah and Islamic Communication, Syaikh Abdurrahman Siddik Islamic Institute, Bangka Belitung. This type of research is qualitative research. Data collection techniques are interviews, observation and documentation. This study concludes that the difference between one individual or group and another lies in the differences in traditions that have been passed down from generation to generation by the local community. In responding to the differences in the cultural background of each individual, cultural awareness is needed. This is because of the frequent differences in cultural backgrounds that cause conflicts in society